Mercury in aqueous tank waste at the Savannah River Site: Facts, forms, and impacts - Bannochie, C. J.; Fellinger, T. L.; Garcia-Strickland, P.; Shah, H. B.; Jain, V.; Wilmarth, W. R. (Separation science and technology, 2018)
Over the past two years, there has been an intense effort to understand the chemistry of mercury across the Savannah River Site's high-level liquid waste system to determine the impacts of various mercury species. This effort began after high concentrations of mercury were measured in the leachates from a toxicity characteristic leaching procedure (TCLP) test on the low-level cementitious waste form produced in the Savannah River Saltstone facility. Speciation showed the dominant form of leached mercury to be the methylmercury cation. Neither the source of the methylmercury nor its concentration in the Saltstone feed was well established at the time of the testing. This assessment of mercury was necessary to inform points in the process operations that may be subject to new separation technologies for the removal of mercury.